Implementasi Metode Complementary Filter pada Pengendali Robot Mobil menggunakan Gestur Tangan Manusia - Samkhya Aparigraha; Wijaya Kurniawan; Agung Setia Budi (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2019)
Human and computer interaction is one of the scientific disciplines that study the design, implementation, and evaluation of interactive computing systems from various related aspects. The current development of the technology of human and computer interaction is progressing very rapidly, especially the interaction between human and robot. Robotics is one area of technology that is still evolving today. Along with its development, more new terms have been introduced, such as mobile robots, humanoids, animaloids, et cetera. Within the control process, mobile robots are divided into two types, namely, automated robots and teleoperating robots. Automated robots can move themselves based on the commands that have been written in the control program, whereas teleoperating robots could move based on commands that are sent manually, either using wired or wireless. To develop a mobile robot that can be controlled using human-hand gestures, the MPU6050 GY-521 module is needed to input the data - in the form of an accelerometer and gyroscope. An accelerometer is used to measure the acceleration of motion, while a gyroscope is used to measure the angular velocity of the rotation. Afterwards, the data will be filtered using a complementary filter method to eliminate noise, which then will be processed using NRF24L01 module as a communication exchange of data between humans and the car robot. Based on the results of this research, it can be concluded that the complementary filter method can reduce the noise of the roll value of 21.8% and the pitch of 26.5% hence it can make the mpu6050 sensor more stable than without using a filter and integrative derivative proportional method which is implanted in the arduino nano controller with a value of Kp = 6.98, Ki = 4.61, and Kd = 1.15, to make the system perfectly run as desired.